2016
DOI: 10.1007/s12035-016-9773-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Activity-Induced Sterol Regulatory Element Binding Protein-1 (SREBP1) is Disrupted in Dysbindin-Null Mice—Potential Link to Cognitive Impairment in Schizophrenia

Abstract: Schizophrenia is a chronic deliberating neuropsychiatric disorder that affects about 1% of the population. Dystrobrevin-binding protein 1 (DTNBP1 or dysbindin) is one of Research Domain Constructs (RDoC) associated with cognition and is significantly reduced in the brain of schizophrenia patients. To further understand the molecular underpinnings of pathogenesis of schizophrenia, we have performed microarray analyses of the hippocampi from dysbindin knockout mice, and found that genes involved in lipogenic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 69 publications
2
9
0
Order By: Relevance
“…It was shown that scratching behavior, an indicator of negative arousal, exhibited a sex-specific association with both AVPR1A genotype, a gene related to mammalian social behavior, and brain morphometry in regions associated with this gene. Although only three studies (Chen et al, 2016; Kondo et al, 2016; Latzman et al, 2016) employed non-human mammals in their research, they highlight how animal research can contribute to the understanding of species-general elements within the RDoC matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that scratching behavior, an indicator of negative arousal, exhibited a sex-specific association with both AVPR1A genotype, a gene related to mammalian social behavior, and brain morphometry in regions associated with this gene. Although only three studies (Chen et al, 2016; Kondo et al, 2016; Latzman et al, 2016) employed non-human mammals in their research, they highlight how animal research can contribute to the understanding of species-general elements within the RDoC matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Rather than focusing on an RDoC construct , one study examined a single element of the Perception construct within the Cognitive Systems matrix. Chen et al ( 2016 ) explored the relationship between the expression of the dysbindin protein, found in neural tissue, and disturbances in the regulation of lipid synthesis and synaptic plasticity. A reduction of sterol regulatory element binding protein-1 (SREBP1), a transcriptional regulator for lipid synthesis, was found in both deceased patients with schizophrenia and dysbindin-1 knockout mice.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of SREBP1, a sterol regulatory element binding protein (SREBP) that regulates the expression of genes implicated in biosynthesis of fatty acids, cholesterol, triglycerides, and phospholipids, is reduced in sdy/B6 mice and in schizophrenia patients; activation of SREBP1 and Arc, a protein implicated in memory and cognition, is reduced in sdy/B6 mice and both of these deficits were restored by treatment with clozapine, suggesting a link with cognitive dysfunction (Chen et al, 2016).…”
Section: Dysbindin-1 and Putative Treatment Strategies For Cognitive mentioning
confidence: 99%
“…Again, deletions in a subset of genes belonging to the Arc complex were significantly enriched in patients with schizophrenia (Marshall et al, 2017 ). Finally, different mouse models relevant to schizophrenia show reduced Arc expression, which is instead not evident in mouse models relevant to other psychiatric disorders such as ADHD or bipolar disorders (Matsuo et al, 2009 ; Takao et al, 2013 ; Takagi et al, 2015 ; Managò et al, 2016 ; Chen et al, 2017 ; Mereu et al, 2017 ). This might suggest that the Arc pathway may serve as a hub that functionally links numerous schizophrenia risk-related factors.…”
Section: Arc Genetics In Schizophreniamentioning
confidence: 99%